RESPON BAP DAN 2,4-D TERHADAP INDUKSI TUNAS TANAMAN VANILI (Vanilla planifolia) - Dwi Erwin Kusbianto; Naufal Cahya Kurniawan; Ayu Puspita Arum; Didik Pudji Restanto (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2022)
[RESPONSE OF IN VITRO SHOOT INDUCTION ON VANILLA PLANTS (Vanilla planifolia) TO THE CONCENTRATION OF BAP AND 2,4-D]. The seeds of V. planifolia A. are plantation product that can be used as food scent and industrial ingredient. On its progression, vanilla farmers propagate by cuttings. The process of vanilla cutting has ben anobstacle in terms of pathogen attack and slow grow, and cuttings propagation is considered unable to meet the demand for seedlings. Tissue culture is a technology that can overcome problems in the vanilla propagation process. The research took place from January to June 2022 at the University of Jember, Bondowoso Campus.  The research  aims to determine the response of shoot induction to the addition of hormones. The completely randomized design (CRD)  was used with 2 factors,the BAP at concentration of 0 , 0.5  and 1 ppm combined with 2,4-D at concentrations of 0.5 , 1 and 1.5 ppm. The data were analyzed using ANOVA with a significant level of 5% and continued with the DMRT test with a significant level of 5%. The results showed that there was an interaction between concentration BAP and 2,4-D in vitro vanilla culture. The treatment without hormones showed a longer shoot formation and the combination of 2,4-D with a higher concentration caused an inhibition in shoot elongation. The combination treatment of 0.5 ppm BAP and 0.5 ppm 2,4-D also 1 ppm BAP and 0.5 ppm 2,4-D had the best response indicated by the highest shoot length and faster shoot formation.